ePuja : seek, discover, get blessed - Patel, Malay; Karna, Amit, active 2017 (London : Indian Institute of Management, Ahmedabad, 2017)
The case describes the entrepreneurial venture initiated by Shiva Kumar and an angel investor Chetan Merchant, and the situation they faced in January 2016. The venture - ePuja - offered the online facility of worshipping and offering prayers in over 3,600 temples across India. The case asks students how ePuja can continue to grow with increased competition and how to reach potential customers in rural India.
Originally Published In Patel, M., & Karna, A. (2017). ePuja: Seek, Discover, Get Blessed. CIIE0006. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; ePuja; Entrepreneurship -- India -- Case studies; Competition -- India -- Case studies; Consumers -- Research -- India -- Case studies